Apology and Its Acceptance: Perceived Reconciliatory Attitudes Reduce Outgroup Dehumanization - Jin, Wen Jie; Park, Sang Hee; Park, Joonha (Frontiers in Psychology, 2022)
Based on real-life intergroup animosities originating from a historical conflict, the current study examined how the perceived stance of the outgroup about the conflict affects the dehumanization of the outgroup. In Study 1 (N = 120), Korean undergraduates attributed more human nature to the Japanese after reading an article that the Japanese government did (vs. refused to) issue an official apology for a historical wrong. In turn, the more human nature assigned to the Japanese predicted higher expectations about positive mutual relations in the future. Similarly, in Study 2 (N = 209), Japanese undergraduates attributed more human uniqueness to Koreans after reading an article that an official apology for a historical wrong from Japan was accepted (vs. rejected) by Koreans. The higher the perceived human uniqueness of Koreans was, the higher were the willingness to help and the expectations of a positive relationship in the future. The findings demonstrate how mutual dehumanization can be reduced as a result of the other side’s reconciliatory stances and can further contribute to improving intergroup relations.